Determinants of Village Fund Management Accountability - Nining Asniar Ridzal; Nirwana Nirwana; Syarifuddin Rasyid (Journal of International Conference Proceedings, 2024)
Investigating and determining the impacts of village officials' duties, fund managers' skills, and information technology use on the accountability of village fund management is the aim of this study, both partially and simultaneously. The descriptive analysis method employs a quantitative approach to data analysis. Data collection was implemented by distributing questionnaires and using SPSS software for processing. This research found that the significance value of the partial test findings (t-test), specifically with a value of 0.002 0.05, suggests that village authorities' participation impacts the accountability of local fund management. The significance value of the partial test findings (t-test), specifically with a value of 0.000 0.05, indicates that the competency of village fund managers affects the accountability of village fund management. The significance value of the partial test findings (t-test), specifically with a value of 0.004 0.05, indicates that the usage of information technology affects the accountability of village fund administration. The use of information technology, the function of village officials, and the proficiency of village fund managers all affect the accountability of village fund management